2021
DOI: 10.1016/j.compbiomed.2020.104186
|View full text |Cite
|
Sign up to set email alerts
|

A computational drug repurposing approach in identifying the cephalosporin antibiotic and anti-hepatitis C drug derivatives for COVID-19 treatment

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused over 1.4 million deaths worldwide. Repurposing existing drugs offers the fastest opportunity to identify new indications for existing drugs as a stable solution against coronavirus disease 2019 (COVID-19). The SARS-CoV-2 main protease (M pro ) is a critical target for designing potent antiviral agents against COVID-19. In this study, we identify potential inhibitors against COVID-19, using an amalgam of virtual s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 58 publications
1
16
0
Order By: Relevance
“…Topology parameters of the potential drug candidates were generated by using SwissParam server 42 . Thereafter, these complexes were simulated for 50 ns using GROningen MAchine for Chemical Simulations (GROMACS v5.1.5) 43 , following the same protocol as described in our previous report 44 .…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Topology parameters of the potential drug candidates were generated by using SwissParam server 42 . Thereafter, these complexes were simulated for 50 ns using GROningen MAchine for Chemical Simulations (GROMACS v5.1.5) 43 , following the same protocol as described in our previous report 44 .…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%
“…44,61,66 . The protein-drug molecular interactions were also stabilized by non-polar interactions within the active site residues of the protein.…”
mentioning
confidence: 99%
“…In general, the associations of antibiotics with COVID-19 outcome are discussed with two aims: one of them is their effect on bacterial coinfections, and the second one is their antiviral effect. A computational analysis showed that chephalosporins had a potential binding ability to SARS-Cov-2 [ 15 ]. If an antibiotic shows a harmful effect, it may be representative of the effect of an underlying bacterial infection.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular dynamics (MD) simulations are applied to understand the protein-ligand interactions at the atomic level in order to scrutinize their conformational flexibility and structural stability under physiological conditions [ 75 , 76 ]. The complexes obtained from the process of molecular docking were subjected to MD simulations in GROningen MAchine for Chemical Simulations ( GROMACS v2018) [ 77 ] with the docked structures of compounds with Hpse as initial coordinates.…”
Section: Methodsmentioning
confidence: 99%